46.8k views
0 votes
How can I factor these complex conjuages? a^2 + b^2 and a^2 - b

User Leochab
by
4.9k points

2 Answers

1 vote

Answer:


\boxed{(a+ib)(a-ib)}


\boxed{a^2+i^2b}

Explanation:


a^2 + b^2

Rewrite expression.


a^2- (-1)b^2

Use identity :
-1=i^2


a^2- i^2 b^2

Factor out square.


a^2-(ib)^2

Apply difference of two squares formula :
a^2-b^2 =(a+b)(a-b)


(a+ib)(a-ib)


a^2-b

Rewrite expression.


a^2+(-1)b

Use identity :
-1=i^2


a^2+i^2b

User Allemattio
by
5.5k points
6 votes

Answer:

1)
(a+ib)(a-ib)

2)
a^2+i^2b

Explanation:

1)
a^2+b^2

=>
a^2 - (-1)b^2 (We know that -1 =
i^2 )

=>
a^2-i^2b^2

=>
(a)^2-(ib)^2

Using Formula
a^2 -b^2 = (a+b)(a-b)

=>
(a+ib)(a-ib)

2)
a^2-b

=>
a^2+(-1)b (We know that -1 =
i^2 )

=>
a^2+i^2b (It cannot be simplified further)

User Radek Czemerys
by
5.1k points